Increased nuchal translucency at 11–13 weeks' gestation and outcome in twin pregnancy. (13th February 2020) - Cimpoca, B.; Syngelaki, A.; Litwinska, E.; Muzaferovic, A.; Nicolaides, K. H.
ABSTRACT: Objective: To investigate the value of increased fetal nuchal translucency thickness (NT) at the 11–13‐week scan in the prediction of adverse outcome in dichorionic (DC), monochorionic diamniotic (MCDA) and monochorionic monoamniotic (MCMA) twin pregnancies. Methods: This was a retrospective analysis of prospectively collected data on twin pregnancies undergoing routine ultrasound examination at 11–13 weeks' gestation between 2002 and 2019. In pregnancies with no major defects or chromosomal abnormalities, we examined the value of increased NT ≥ 95 th percentile in one or both fetuses in the prediction of, first, miscarriage or death of one or both fetuses at < 20 and < 24 weeks' gestation in DC, MCDA and MCMA twin pregnancies, second, death of one or both fetuses or neonates at ≥ 24 weeks in DC, MCDA and MCMA twin pregnancies, third, development of twin–twin transfusion syndrome (TTTS) or selective fetal growth restriction (sFGR) treated by endoscopic laser surgery at < 20 and ≥ 20 weeks' gestation in MCDA pregnancies, and, fourth, either fetal loss or laser surgery at < 20 weeks' gestation in MCDA pregnancies. Results: The study population of 6225 twin pregnancies included 4896 (78.7%) DC, 1274 (20.5%) MCDA and 55 (0.9%) MCMA pregnancies. The incidence of NT ≥ 95 th percentile in one or both fetuses in DC twin pregnancies was 8.3%; in MCDA twins the incidence was significantly higher (10.4%; P = 0.016), but in MCMA twins it was not significantly different (9.1%; P = 0.804) from that in DC twins. In DC twin pregnancies, the incidence of high NT was not significantly different between those with two survivors and those with adverse outcome. In MCMA twin pregnancies, the number of cases was too small for meaningful assessment of the relationship between high NT and adverse outcome. In MCDA twin pregnancies with at least one fetal death or need for endoscopic laser surgery at < 20 weeks' gestation, the incidence of NT ≥ 95 th percentile was significantly higher than in those with two survivors (23.5% vs 9.8%; P < 0.0001). Kaplan–Meier analysis in MCDA twin pregnancies showed that, in those with NT ≥ 95 th percentile, there was significantly lower survival at < 20 weeks' gestation than in those with NT < 95 th percentile ( P = 0.001); this was not the case for survival at ≥ 20 weeks ( P = 0.960). The performance of screening by fetal NT ≥ 95 th percentile for prediction of either fetal loss or need for endoscopic laser surgery at < 20 weeks' gestation was poor, with a detection rate of 23.5% at a false‐positive rate of 8.9%, and the relative risk, in comparison to fetal NT < 95 th percentile, was 2.640 (95% CI, 1.854–3.758; P < 0.0001). In MCDA twin pregnancies, the overall rate of fetal loss or need for laser surgery at < 20 weeks' gestation was 10.7% but, in the subgroups with NT ≥ 95 th and NT ≥ 99 th percentiles, which constituted 10.4% and 3.3% of the total, the rates increased to 24.1% and 40.5%, respectively. Conclusions: In MCDA twin pregnancies with no major fetal abnormalities, measurement of NT at the 11–13‐week scan is a poor screening test for adverse pregnancy outcome. However, the finding in one or both fetuses of NT ≥ 95 th percentile, and more so ≥ 99 th percentile, is associated with a substantially increased risk of fetal loss or need for endoscopic laser surgery at < 20 weeks' gestation. The extent to which closer monitoring and earlier intervention in the high‐risk group can reduce these complications remains to be determined. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.